Problematika Pelaksanaan Pendaftaran Tanah Sistematis Lengkap (PTSL) di Desa Singopadu Sidoarjo - mulia, sheilla siartha (Universitas Negeri Surabaya, 2020)
Land registration is a series of activities carried out by the government continuously, continuously and regularly including collection, processing, bookkeeping and reviewing and maintaining physical data and juridical data in the form of maps and lists of land parcels and apartment units, including the provision certificate of proof of rights for plots of land for which there are rights and ownership rights over the unit of flats and certain rights which burden it. This has been stated in Article 1 of Government Regulation No. 24 of 1997. For the sake of achieving legal certainty over a piece of land owned by a person, the Central Government provides a program that facilitates the community in the management of certificates which are proof of rights as a form of program of Agrarian Reform by issuing Regulations Minister of Agrarian Affairs and Spatial Planning / To the Republic of Indonesia National Land Agency No. 6 of 2018 concerning Complete Systematic Land Registration (PTSL). Singopadu village is one of the villages that participated in this program, as for the problems in implementing the PTSL program in this village. The research method used is descriptive qualitative method and the type of research is empirical juridical. Data collection techniques using the interview method and use the documentation method. Interviews were conducted with informants from Sidoarjo National Land Agency employees, and the Singopadu Sidoarjo village community. The results of this study indicate that in the implementation of PTSL there are obstacles encountered so as to hamper the land registration process. Keywords: Land registration, PTSL, obstacles.